Effects of inflammation and oxidative stress on postoperative delirium in cardiac surgery - Pang, Yi; Li, Yuntao; Zhang, Yonggang; Wang, Hongfa; Lang, Junhui; Han, Liang; Liu, He; Xiong, Xiaoxing; Gu, Lijuan; Wu, Xiaomin (Frontiers in Cardiovascular Medicine, 2022)
The past decade has witnessed unprecedented medical progress, which has translated into cardiac surgery being increasingly common and safe. However, complications such as postoperative delirium remain a major concern. Although the pathophysiological changes of delirium after cardiac surgery remain poorly understood, it is widely thought that inflammation and oxidative stress may be potential triggers of delirium. The development of delirium following cardiac surgery is associated with perioperative risk factors. Multiple interventions are being explored to prevent and treat delirium. Therefore, research on the potential role of biomarkers in delirium as well as identification of perioperative risk factors and pharmacological interventions are necessary to mitigate the development of delirium.